2022
DOI: 10.1088/1742-6596/2377/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Back-projection results for the Mw7.5, 28 September 2018 Palu earthquake-tsunami

Abstract: A back-projection technique allows seismologists to analyse rupture properties once seismic signals from a dense array of seismic networks are available. The observed waveforms are then traced back in space and time to the source region of an earthquake under investigation. In this study, the method utilised the back-projection image of the recorded high-frequency P-seismic waveforms filtered at 0.25-1.0 Hz by Multiple Signal Classification (MUSIC) processing to estimate the extent and the spread of earthquake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Other projects for both the EPRG members and final year students include kinematic examination of earthquake rupture processes using the so-called multiple signal classification of back-projection imaging (MUSIC BPI) [19,20], referred to seismic signal processing with high resolution that relies on the signal coherence from P-seismic waveforms recorded by a dense seismic array and filtered at high frequency of 0.25-1.0 Hz. Applied to the case of the 2018 Palu-Donggala earthquake that in turn generated a locally propagating tsunami inside Palu Bay, this technique was successful to demonstrate a NNW-SSE trend in the aftershock data of the event [21]. Similarity found in the rupture direction to the lineament of the strike-slip Palu-Koro fault suggested that the 2018 Palu tsunami-earthquake event is partly associated with the active fault, consistent with previous work [22,23].…”
Section: Projects Towards Seismological and Volcanological Topicssupporting
confidence: 83%
“…Other projects for both the EPRG members and final year students include kinematic examination of earthquake rupture processes using the so-called multiple signal classification of back-projection imaging (MUSIC BPI) [19,20], referred to seismic signal processing with high resolution that relies on the signal coherence from P-seismic waveforms recorded by a dense seismic array and filtered at high frequency of 0.25-1.0 Hz. Applied to the case of the 2018 Palu-Donggala earthquake that in turn generated a locally propagating tsunami inside Palu Bay, this technique was successful to demonstrate a NNW-SSE trend in the aftershock data of the event [21]. Similarity found in the rupture direction to the lineament of the strike-slip Palu-Koro fault suggested that the 2018 Palu tsunami-earthquake event is partly associated with the active fault, consistent with previous work [22,23].…”
Section: Projects Towards Seismological and Volcanological Topicssupporting
confidence: 83%